Chapter Constructing territories, deconstructing the landscape: a conclusion - Santos Salazar, Igor (Firenze University Press, 2025)
This article examines the main places where elites accumulated, consumed and displayed resources in order to demonstrate their ability to control and organise their dominated spaces. Indeed, in these segmented societies, where control of space is achieved through the construction and domination of a network of places of power, our attention must focus on these points. From these places of power, aristocratic groups construct countervailing discourses aimed at justifying, expressing and perpetuating their domination, both material and symbolic. Social estimators of material wealth are one of the fundamental elements of this desire for distinction, and one of the most compelling markers for identifying these places.